If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4w-5 (2w-6)=10-(w-5)
We simplify the equation to the form, which is simple to understand
4w-5(2w-6)=10-(w-5)
Reorder the terms in parentheses
4w+(-10w+30)=10-(w-5)
Remove unnecessary parentheses
+4w-10w+30=+10-(+w-5+)
Remove unnecessary parentheses
4w-10w+30=10-1w+5
We move all terms containing w to the left and all other terms to the right.
+4w-10w+1w=+10+5-30
We simplify left and right side of the equation.
-5w=-15
We divide both sides of the equation by -5 to get w.
w=3
| -0.6b+7+0.4b=19 | | x^2+y^2+10x+6y+34=0 | | 176=-16m | | -10(x-6)=70 | | x^2+y^2+10x+6y=-34 | | -8h+47=-1 | | x^2+y^2=-10x-6y-34 | | -15x+22=-38 | | 45+2(3-x)=2 | | 11-8z=69 | | (2x^2-11x-15)/(x+7) | | 4q-17=17 | | 2q+9=5 | | (x-y-1)dx+(4y+x-1)dy=0 | | 6=18-4x | | 2(3y-4)=3(y-2/3) | | -4+0= | | 10+14y=-130 | | 8-2x=2x-4 | | m+x+n/p | | 65=7c+5 | | -6y+18=24 | | 21=m+15 | | 7/m-9=5 | | 6p+(-13)=5 | | 6-4x=2x+18 | | 10-19v+6v^2= | | x/11=21/77 | | 20d-40=0 | | (x+3y+3)dx+(3x+y+9)dy=0 | | 2-3x-5=1-x | | 98=14y+2 |